1995
DOI: 10.1021/la00012a043
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Morphology Analysis of Combustion-Generated Aggregates Using Angular Light Scattering and Electron Microscope Images

Abstract: Experimental studies of the fractal morphology of flame-generated aggregates are described here, considering not only the fractal dimension, Df, but also the fractal prefactor (lacunarity), kg, both of which are shown to be needed to fully characterize aggregates. Measurements were made using angular light scattering (ALS) and thermophoretic sampling followed by transmission electron microscopy (TEM) for soot aerosols found in laminar and turbulent flame environments. Df and the prefactor kg were simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(101 citation statements)
references
References 0 publications
6
91
0
Order By: Relevance
“…In contrast, fractal exponents of approximately 2.5 are expected when growth is dominated by the diffusion of primary particles (monomers) to an existing aggregate (Schleicher et al 1995). The observations reported herein are also in the range of fractal exponents reported for soot aggregates (1.6-1.9) obtained in both laminar and turbulent diffusion ames summarized by Koylu et al (1995). The experimental results generated herein therefore suggest that the morphology of ame generated aggregates is largely controlled by cluster-cluster aggregation of smaller aggregates formed in the early stage of the ame and is invariant with changes in chemical composition and mass density of particulate in the ame for the range of conditions considered herein.…”
Section: Bench Scale Experiments Utilizing Controlled Composition Aersupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, fractal exponents of approximately 2.5 are expected when growth is dominated by the diffusion of primary particles (monomers) to an existing aggregate (Schleicher et al 1995). The observations reported herein are also in the range of fractal exponents reported for soot aggregates (1.6-1.9) obtained in both laminar and turbulent diffusion ames summarized by Koylu et al (1995). The experimental results generated herein therefore suggest that the morphology of ame generated aggregates is largely controlled by cluster-cluster aggregation of smaller aggregates formed in the early stage of the ame and is invariant with changes in chemical composition and mass density of particulate in the ame for the range of conditions considered herein.…”
Section: Bench Scale Experiments Utilizing Controlled Composition Aersupporting
confidence: 71%
“…If a system were to encounter an increasing temperature gradient, or a prolonged period at elevated temperature, both internal rearrangement and modi cation of the fractal exponent would be expected. This has been demonstrated by Schmidt-Ott (1988) for silver aerosols and has been more recently demonstrated for alumina in a laboratory counter ow diffusion ame (Xing et al 1997;Koylu et al 1995).…”
Section: Bench Scale Experiments Utilizing Controlled Composition Aermentioning
confidence: 72%
See 1 more Smart Citation
“…By means of numerical simulations, they found that ka and a fall in the following ranges: a = 1.08-1.19 and ka = 1.00-1.81. Koylu et al (1995b) suggested a = 1.09 and ka = 1.15 by their extensive analysis of particle morphology. Oh and Sorensen ( 1997) took the overlapping of primary particles into account and found that a = 1.19 and ka = 1.81 when the overlap parameter, which is the ratio of the primary particle diameter to the distance between two touching particles, is 2.…”
Section: Fractal Dimension Of Diesel Agglomeratesmentioning
confidence: 99%
“…They showed that in their simulated agglomerates, accounting for overlap leads to more primary particles per agglomerate, and therefore to agglomerates that are more dense and that have a higher fractal dimension and prefactor (D 1 = 2.01, kg = 3.0) compared to values when overlapping is ignored (D 1 = 1.80, kg = 1.30). In the present study, the values of a and ka suggested by Koylu et al (1995b; a = 1.09, ka = 1.15) and Oh and Sorensen (1997; a = 1.19, ka = 1.81) are employed when using Equation (3) to determine the number of primary particles in diesel agglomerates.…”
Section: Fractal Dimension Of Diesel Agglomeratesmentioning
confidence: 99%